Efficiency Evaluation of Virtual Concatenation in SDH Network - Plėštys, R.; Šinickas, D. (Elektronika ir Elektrotechnika, 2005)
In this paper we propose the system of virtual concatenation, which designed to transfer fixed amount of data in given time. Date transfer is researched by using many parallel virtual concatenated channels. Probability of task completion in given time is taken for system ready to explore main parameter. This methodology is useful in the network, which use virtual concatenated channel. From derived dependence, we compute fall down task probability, when number of virtual concatenated channel is different. We get virtual concatenated channel probability dependence on task completion in given time, when task completion time or one virtual channel fault rate is changing. We show how number of virtual concatenated channel and other parameters determine task completion. Ill. 4, bibl. 4 (in Lithuanian; summaries in Lithuanian, English and Russian).